Exploring Students' Interactions in a CALL-based Environment in a Malaysian Secondary ESL Classroom - Lily, Tan Hui Chin (Universiti Malaysia Sarawak, (UNIMAS), 2007)
This explorative study aimed to gain insight of the general nature of the students' interactions in a CALL-based environment in a Malaysian Secondary ESL classroom with the purpose of finding out the types of oral interaction that took place and the factors that may have influenced those types of interaction. The study employed methodology that incorporated classroom observations, audio-recording and field notes. Both qualitative and quantitative analyses were undertaken in this study. Students' interactions were coded based on a selected framework and the frequencies of the types of interaction that occurred were tabulated quantitatively. Students who participated in the study were 72 Form Five students working in pairs, trios and groups to complete two types of CALL-based tasks (Web-based tasks and CD-ROM tasks). The analysis showed tar lesser amount of cognitive interactions expected in the students' interactions and factors of' grouping size and type of CALL-based task did influence the students' interactions. Nevertheless, the CALL-based environment did encourage the students to use the target language